Ramifications of Structural Deformations on Collapse Loads of Critically Cracked Pipe Bends Under In-Plane Bending and Internal Pressure - Sumesh Sasidharan; Veerappan Arunachalam; Shanmugam Subramaniam (Nuclear Engineering and Technology, 2017)
Finite-element analysis based on elastic–perfectly plastic material was conducted to examine the influence of structural deformations on collapse loads of circumferential through-wall critically cracked 90° pipe bends undergoing in-plane closing bending and internal pressure. The critical crack is defined for a through-wall circumferential crack at the extrados with a subtended angle below which there is no weakening effect on collapse moment of elbows subjected to in-plane closing bending. Elliptical and semioval cross sections were postulated at the bend regions and compared. Twice-elastic-slope method was utilized to obtain the collapse loads. Structural deformations, namely, ovality and thinning, were each varied from 0% to 20% in steps of 5% and the normalized internal pressure was varied from 0.2 to 0.6. Results indicate that elliptic cross sections were suitable for pipe ratios 5 and 10, whereas for pipe ratio 20, semioval cross sections gave satisfactory solutions. The effect of ovality on collapse loads is significant, although it cancelled out at a certain value of applied internal pressure. Thinning had a negligible effect on collapse loads of bends with crack geometries considered.